Sistem Pendukung Keputusan Pemilihan Ketua Osis Di Sekolah Menengah Atas (SMA) Negeri 1 Mulak Ulu Menggunakan Metode Analytical Hierarchy Process (AHP) - Risnaini Masdalipa; Debi Gusmaliza; Riduan Syahri (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
Decision support system (SPK) is a computer-based system that is intended to help decision makers by utilizing certain data and models to solve various unstructured problems. From the results of research observations, it was found that the system used to elect prospective student council candidates at the State High School 1 Mulak Ulu still uses a manual selection system. This study aims to design a decision support system for OSIS chair election using the Analytical Hierarchy Process method in which OSIS chair election takes into account the criteria of intelligence, activeness, crafts as well as the vision and mission of the student council president candidates. In making this decision support system using the Programming Hypertext Preprocessor programming and Mysql database. While the system development method uses the Waterfall method with the stages of analysis, design, coding and testing. The final results obtained after being tested in the State High School 1 Mulak Ulu is a decision support system that has the ability to solve problems in the process of selecting the student council president